TRANSVERSAL COMPETENCIES IN ICT STUDY PROGRAMS: AN INTRODUCTION TO CURRENT RESEARCH - Abuže, Anda (Education Reform: Education Content Research and Implementation Problems, 2020)
The research is carried out within the framework of the doctoral thesis “Methodology and tools for sensor network design”, where transversal competencies and their assessment are related to ICT study programs, such as “Mechatronics” implemented by Rezekne Academy of Technologies and based on Smart Specialization Strategy (RIS3) ICT and smart materials, technologies and engineering systems.Today's labour market needs competitive employees who are able to analyze situations with systematic and design thinking. The education system needs to change in line with the requirements of the Fourth Industrial Revolution, so prospective workers need to have knowledge of interdisciplinary and multidisciplinary processes.The aim of this research is to determine the transversal competencies of ICT study programs. The monographic and descriptive method has been applied for studying scientific literature. The research looks at the competencies and skills that are needed for ICT graduates, such as digital, innovative, entrepreneurship, research, communication, critical thinking, human relation, leadership, planning, problem solving.